AGRICULTURE IN THE MIDST OF INDONESIA'S ECONOMIC TRANSFORMATION: Empirical Study on the Influence of Industry, CPI, Food Price Index, PMA, Import Role, Labor, and Financial Sector - Simanjutak, Jerry Marmen (Jurnal Mamangan, 2023)
The agricultural sector is a key sector in a number of developing countries including Indonesia. The sector has a role in providing food and raw materials for other economic sectors, which can then encourage industrialization. However, the contribution of agriculture in Indonesia has also experienced a significant decline. So this research aims to find out what factors affect the contribution of agriculture to the National GDP with OLS regression, specifically assessing the extent of the role of bank credit in the agricultural sector. It also analyzes each periodization of the Indonesian presidential government. The results of the study show that labor and industry contribution to national GDP have greater elasticity compared to other variables. This also reflects that the economic transformation has an impact on the agricultural sector in Indonesia.